Implementation of Seismic Inversion to Determine Porosity Distribution of Maysan in Amara Oil Field, Southern Iraq - Jaheed, Ali K.; Karim, Hussein H. (Iraqi Journal of Science, 2022)
The current research deals with studying the petrophysical properties represented by the porosity and its distribution on the level of all units of the top and bottom of the Kirkuk Formation Group. The study area is located in Maysan province in the south-eastern part of Iraq in the Amara field. The Kirkuk Group was deposited in the Tertiary Age. The post-stack method using seismic inversion and creating a relationship between seismic data was accomplished using Hampson-Russel software at well Am-1 and Seismic lines Ama 20 and 30. The research results indicate high porosity values on top of the formation with a decrease in acoustic impedance (Z) and, therefore, a reduction in the density. At the same time, low porosity values were indicated for the bottom of the formation with an increase in both acoustic impedance and density. The top of the formation contains clastic sediments with oil-sand of high porosity, which is considered hydrocarbon indication and low porosity carbonate materials at the bottom of the formation.